PEMBELAJARAN DARING MENULIS TEKS EKSPOSISI PADA SISWA KELAS VIII DENGAN METODE DISCOVERY LEARNING BERBANTUAN MEDIA QUIZIZZ - Ernasari Ernasari; Diena San Fauziya; Reka Yuda Mahardika (IKIP Siliwangi, 2022)
Writing exposition text is still considered difficult by students, especially in today's online learning which is not face to face. The use of appropriate methods and media can be a solution in the online learning process by utilizing available applications. This study aims to determine student learning outcomes in online learning to write exposition text with discovery learning method assisted by Quizizz media and what difficulties students experience in writing exposition text; to find out students' responses to online learning to write exposition text using discovery learning method assisted by Quizizz media. The method used is descriptive qualitative method. Data collection techniques in the form of tests and questionnaires. The success of learning is seen from the results of the knowledge and skills test which shows the average value of both of them is 77.2 and has met the achievement indicators. The difficulty of the knowledge test questions with a score of 5 regarding the command shows the structure of the text of the exposition of the thesis section, while the difficulty of the skill questions with a score of 70 is in the rules of the reference word language. The results of a very good response during the learning process showed a percentage of 83%. Judging from student learning outcomes and student response results, the methods and media used can motivate students in online learning to write exposition text.